ERCC4: a potential regulatory factor in inflammatory bowel disease and inflammation-associated colorectal cancer - Shi, Runjie; Wang, Shanping; Jiang, Ying; Zhong, Guoqiang; Li, Mingsong; Sun, Yan (Frontiers in Endocrinology, 2024)
The pathogenesis of inflammatory bowel disease (IBD) remains unclear and is associated with an increased risk of developing colitis-associated cancer (CAC). Under sustained inflammatory stimulation in the intestines, loss of early DNA damage response genes can lead to tumor formation. Many proteins are involved in the pathways of DNA damage response and play critical roles in protecting genes from various potential damages that DNA may undergo. ERCC4 is a structure-specific endonuclease that participates in the nucleotide excision repair (NER) pathway. The catalytic site of ERCC4 determines the activity of NER and is an indispensable gene in the NER pathway. ERCC4 may be involved in the imbalanced process of DNA damage and repair in IBD-related inflammation and CAC. This article primarily reviews the function of ERCC4 in the DNA repair pathway and discusses its potential role in the processes of IBD-related inflammation and carcinogenesis. Finally, we explore how this knowledge may open novel avenues for the treatment of IBD and IBD-related cancer.